2003
DOI: 10.1016/s0169-2607(02)00099-8
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of the skin reflectance spectra

Abstract: The reflectance spectra of the human skin in visible and near-infrared (NIR) spectral region have been calculated using the Monte Carlo technique, and the specular and internal reflection on the medium surface is taken into account. Skin is represented as a complex inhomogeneous multi-layered highly scattering and absorbing medium. The model takes into account variations in spatial distribution of blood, index of blood oxygen saturation, volume fraction of water and chromophores content. The simulation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
111
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(115 citation statements)
references
References 26 publications
2
111
0
2
Order By: Relevance
“…Meglinski and Matcher's program 47,69 involved a seven layered skin model to simulate the reflectance spectrum of human skin, as measured using a fiber optic probe setup. Path lengths were calculated according to Eq.…”
Section: Monte Carlo Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meglinski and Matcher's program 47,69 involved a seven layered skin model to simulate the reflectance spectrum of human skin, as measured using a fiber optic probe setup. Path lengths were calculated according to Eq.…”
Section: Monte Carlo Methodsmentioning
confidence: 99%
“…Thus, the validity of this approximation is limited in such cases. 34,43,[45][46][47] These drawbacks have limited the application of the diffusion approximation to investigations of PWS skin. For example, Verkruysse et al 45 reported that data obtained from their twolayered skin model could be obtained quickly but compared poorly to measured spectra, resulting in an overestimation of blood volume fraction, oxygenation levels and melanin concentration in port wine stain (PWS) skin.…”
Section: Diffusion Approximationmentioning
confidence: 99%
“…The refractive index of skin tissue and haemoglobin is assumed to be constant. These values were obtained from literature 44,45,46 and a curve fitting model applied to interpolate the values for each wavelength. An average value of these for mathematical modelling is detailed in Table 1.…”
Section: System Theorymentioning
confidence: 99%
“…Average approximate absorption (μ a ) and scattering (μ s ) coefficients in cm -1 for various chromophores in human skin tissue for the red and green wavelength region. The values were averaged by applying an interpolation curve to the existing data from literature 44,45,46 . Note that oxygenation of the RBC has no effect on its scattering properties.…”
Section: System Theorymentioning
confidence: 99%
“…Values of these optical properties which are used for simulations are taken from the literature [41][42][43]. Our previous work [44] shows that simulation of the theory over the physiological RBC concentration (0%-4%) shows a linear relationship between proposed variable TiVi index and RBC f , and also shows insensitivity to oxygenation between physiological range 60% -100%, while also showing only minimal differences in the relationship when the optical properties are changed by ±5%.…”
Section: Theorymentioning
confidence: 99%